2015
DOI: 10.4000/interventionseconomiques.2609
|View full text |Cite
|
Sign up to set email alerts
|

A Participatory Governance Model Towards the Inclusion of Ethnic Minorities. An Action Research Experience in Italy

Abstract: A Participatory Governance Model Towards the Inclusion of Ethnic Minorities. ... Revue Interventions économiques, 53 | 2015 1 role in promoting the social inclusion of minorities by fostering a participatory governance model inspired by the principles of subsidiarity, autonomy, responsibility and active involvement of community leaders expressed by minority groups themselves. These are new relevant elements to be taken into account in the planning of social interventions. This model, as mentioned above, is als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 13 publications
(14 reference statements)
0
1
0
Order By: Relevance
“…The literature on collaborative governance has shown that the management of a more sustainable city is built on the articulation and exchange of different actors in collaboration processes. It is important to note that in a collaborative process one must consider the participation of representatives of civil society, as well as the political and technical-administrative stakeholders (Kissler & Heidemann, 2006;Ronconi, 2011;Marcaletti & Riniolo, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The literature on collaborative governance has shown that the management of a more sustainable city is built on the articulation and exchange of different actors in collaboration processes. It is important to note that in a collaborative process one must consider the participation of representatives of civil society, as well as the political and technical-administrative stakeholders (Kissler & Heidemann, 2006;Ronconi, 2011;Marcaletti & Riniolo, 2015).…”
Section: Introductionmentioning
confidence: 99%